Variation of Heartwood Proportion and Wood Colour from Fast Grown 5-Year-Old Teak - Ratih Damayanti; Barbara Ozarska; Jugo Ilic; Gustan Pari; Wahyu Dwianto; Dian Anggraini Indrawan; Krisdianto Krisdianto (Wood Research Journal, 2020)
The heartwood percentage and wood colour of fast plantation grown teak destined for harvest at 5 years of age were characterized using automatic image processing ’ImageJ’ routines and CieLab’s colour system with the following coefficients: L for lightness, a* for redness and b* for yellowness. Analyses were conducted on material from different dry and wet sites. Comparison with 6-year old plantation from a dry site was conducted to study differences arising in older trees. Analyses of variation of those properties between and within different tree diameter classes were also conducted. The results showed that brightness, redness and yellowness values of 5-year old teak trees were 60.7, 10.7 and 23.1, respectively. Tree clone had a more dominant effect on wood colour and heartwood proportion than site, thus if specific colour preferences are needed of plantation trees, clone selection is important. The drier site produced larger proportions of heartwood in trees, as well as a more attractive figure. The trees produced heartwood proportions of 20% and 14% from the dry and wet sites respectively. On average, these 5 year old teak trees already produced 18% heartwood. Faster tree growth (larger diameter) appeared to have produced significantly larger heartwood proportions. Radially, the palest colour (the highest L but the lowest a*b* parameters) occurred in an area between heartwood and sapwood indicating the presence of a transition zone in all the tree samples.